Dose calibrator linearity test: 99mTc versus 18F radioisotopes - Willegaignon,José (2015)
Objective: The present study was aimed at evaluating the viability of replacing 18F with 99mTc in dose calibrator linearity testing. Materials and Methods: The test was performed with sources of 99mTc (62 GBq) and 18F (12 GBq) whose activities were measured up to values lower than 1 MBq. Ratios and deviations between experimental and theoretical 99mTc and 18F sources activities were calculated and subsequently compared. Results: Mean deviations between experimental and theoretical 99mTc and 18F sources activities were 0.56 (± 1.79)% and 0.92 (± 1.19)%, respectively. The mean ratio between activities indicated by the device for the 99mTc source as measured with the equipment pre-calibrated to measure 99mTc and 18F was 3.42 (± 0.06), and for the 18F source this ratio was 3.39 (± 0.05), values considered constant over the measurement time. Conclusion: The results of the linearity test using 99mTc were compatible with those obtained with the 18F source, indicating the viability of utilizing both radioisotopes in dose calibrator linearity testing. Such information in association with the high potential of radiation exposure and costs involved in 18F acquisition suggest 99mTc as the element of choice to perform dose calibrator linearity tests in centers that use 18F, without any detriment to the procedure as well as to the quality of the nuclear medicine service.